Testing of the ultra-early maturing maize hybrids of French breeding for grain production in the Tomsk region - N. A. Perchenko; O. N. Sergeeva (Зерновое хозяйство России, 2021)
The current paper has presented the testing results of such ultra-early maturing maize hybrids of French breeding with different FAOs, as ‘Zeta 102’ (FAO – 115), ‘Zeta 140 S’ (FAO – 140), ‘Lazuliya’ (FAO – 170) in 2019 and 2020. The phenological study has shown that at the beginning of the vegetation period the maize leaf area of the hybrid ‘Zeta 102’ increased more intensively and reached its maximum value at the heading stage. At the same time, at the period of the 6th leaf formation, the leaf surface of the later maturing hybrid ‘Lazuliya’ (FAO – 170) formed more intensively. In addition, the maize hybrids with a more elongated FAO formed taller plants, the average plant height of the hybrid ‘Lasuliya’ was significantly higher than that of the two hybrids ‘Zeta’. The hybrid ‘Lasuliya’ also showed higher yield structure and grain yield. The hybrid ‘Lasuliya’ was characterized with not only a larger cob weight compared to other hybrids, but also with a significantly larger number of grains per cob, and, accordingly, a higher grain yield. At the same time, the biological yield of the maize hybrid ‘Zeta 102’ (FAO – 115) turned out to be higher, which may indicate a higher foliage of this hybrid, this is also confirmed by the lowest coefficient of economic efficiency. The results of the tests showed that in the Tomsk region it is preferable to grow the maize hybrid ‘Lasuliya’ for grain, and ‘Zeta 102’ for silage. The tests are going to be continued in other districts of the Tomsk region.